Strategi Penanganan Pembiayaan Bermasalah pada Produk Pembiayaan - Rosiana, Inne; Nasrudin, Solihin; Sutrisno, Hadi; Putera, Alifi Restu; Hajarudin, Hajarudin (Commodities, Journal of Economic and Business, 2024)
Problematic financing is non-current financing given by BMT to members who cannot fulfill the requirements or the obligation to repay funds that have been loaned before on the due date. Handling of troubled financing must be carried out by all financial institutions, because BMT will experience losses if it turns out that the quality of financing that has been channeled is not good. The objectives of this research are: 1) To find out what are the factors that cause problem financing in the BMT NU Cabang Kesamben. 2) To take appropriate steps and strategies in handling problem financing in the BMT NU Cabang Kesamben. This study uses qualitative methods and takes location in the BMT NU Cabang Kesamben. The focus in this study is the Problematic Financing Management Strategy on Financing Products. The data sources in this study are the Chairperson and Marketing of the BMT NU Cabang Kesamben and Problematic Financing data. Data collection methods used are observation, interviews and documentation. The results of this study indicate that: first, the factors that led to the emergence of problematic financing in BMT NU Cabang Kesamben consists of internal factors arising from the BMT, as well as external factors that arise from the customer itself. Secondly, the handling strategy at the NU BMT Cabang Kesamben has been quite effective, as evidenced by the problematic financing data which has decreased every year. In handling troubled financing, the strategies used by BMT NU Cabang Kesamben are by doing it (re-survey, friendship, giving warning letters, billing after the due date, and finally doing rescheduling / rescheduling).